Tracking Hypoxic Signaling within Encapsulated Cell Aggregates - Skiles, Matthew L. (MyJove Corporation, 2011)
In Diabetes mellitus type 1, autoimmune destruction of the pancreatic β-cells results in loss of insulin production and potentially lethal hyperglycemia. As an alternative treatment option to exogenous insulin injection, transplantation of functional pancreatic tissue has been explored(1,2). This approach offers the promise of a more natural, long-term restoration of normoglycemia. Protection of the donor tissue from the host's immune system is required to prevent rejection and encapsulation is a method used to help achieve this aim. Biologically-derived materials, such as alginate(3) and agarose(4), have been the traditional choice for capsule construction but may induce inflammation or fibrotic overgrowth(5) which can impede nutrient and oxygen transport. Alternatively, synthetic poly(ethylene glycol) (PEG)-based hydrogels are non-degrading, easily functionalized, available at high purity, have controllable pore size, and are extremely biocompatible,(6,7,8). As an additional benefit, PEG hydrogels may be formed rapidly in a simple photo-crosslinking reaction that does not require application of non-physiological temperatures(6,7). Such a procedure is described here. In the crosslinking reaction, UV degradation of the photoinitiator, 1-[4-(2-Hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one (Irgacure 2959), produces free radicals which attack the vinyl carbon-carbon double bonds of dimethacrylated PEG (PEGDM) inducing crosslinking at the chain ends. Crosslinking can be achieved within 10 minutes. PEG hydrogels constructed in such a manner have been shown to favorably support cells(7,9), and the low photoinitiator concentration and brief exposure to UV irradiation is not detrimental to viability and function of the encapsulated tissue(10). While we methacrylate our PEG with the method described below, PEGDM can also be directly purchased from vendors such as Sigma. An inherent consequence of encapsulation is isolation of the cells from a vascular network. Supply of nutrients, notably oxygen, is therefore reduced and limited by diffusion. This reduced oxygen availability may especially impact β-cells whose insulin secretory function is highly dependent on oxygen(11-13). Capsule composition and geometry will also impact diffusion rates and lengths for oxygen. Therefore, we also describe a technique for identifying hypoxic cells within our PEG capsules. Infection of the cells with a recombinant adenovirus allows for a fluorescent signal to be produced when intracellular hypoxia-inducible factor (HIF) pathways are activated(14). As HIFs are the primary regulators of the transcriptional response to hypoxia, they represent an ideal target marker for detection of hypoxic signaling(15). This approach allows for easy and rapid detection of hypoxic cells. Briefly, the adenovirus has the sequence for a red fluorescent protein (Ds Red DR from Clontech) under the control of a hypoxia-responsive element (HRE) trimer. Stabilization of HIF-1 by low oxygen conditions will drive transcription of the fluorescent protein (Figure 1). Additional details on the construction of this virus have been published previously(15). The virus is stored in 10% glycerol at -80° C as many 150 μL aliquots in 1.5 mL centrifuge tubes at a concentration of 3.4 x 10(10) pfu/mL. Previous studies in our lab have shown that MIN6 cells encapsulated as aggregates maintain their viability throughout 4 weeks of culture in 20% oxygen. MIN6 aggregates cultured at 2 or 1% oxygen showed both signs of necrotic cells (still about 85-90% viable) by staining with ethidium bromide as well as morphological changes relative to cells in 20% oxygen. The smooth spherical shape of the aggregates displayed at 20% was lost and aggregates appeared more like disorganized groups of cells. While the low oxygen stress does not cause a pronounced drop in viability, it is clearly impacting MIN6 aggregation and function as measured by glucose-stimulated insulin secretion(15). Western blot analysis of encapsulated cells in 20% and 1% oxygen also showed a significant increase in HIF-1α for cells cultured in the low oxygen conditions which correlates with the expression of the DsRed DR protein.